Sexual identification of bamboo borer Dinoderus minutus (Fabricius) (Coleoptera: Bostrychidae) - Abood, Faizah; Ahmad Razi, Norhisham; Shahman, Mohd; Anthony, Andy (2010)
There is no available documented literature on sexual identification of the bamboo borer Dinoderus minutus (Fabricius). In this study, adult and pupal stages of Dinoderus minutus were examined in an attempt to differentiate the sexes for this particular species. Freshly killed and cleaned adult as well as pupal stages were examined under stereomicroscopy and different characteristics for both stages were compared. Results showed that there were no distinct morphological features in the adult stage that could be used as distinguishing sexual characters. However, differentiating sexual features were observed in the pupal stage. Gonapophyses, comprising of a pair of conical extrusions were present at the terminal abdominal segment in the female pupa whilst a pair of parameres was observed in the male. These morphological characteristics which were identified only in the pupal stage, proved to be the most reliable method to determine the sex of D. minutus.